Epistemic akrasia and epistemic inefficacy : a virtue-based approach - Veronica de Souza Campos (2022)
In this dissertation I make the case for a “new” epistemic vice, the vice of epistemic inefficacy. While baptizing and sketching profiles to vices is a bold philosophical enterprise, the task is made unpresuming by the fact that the vice I attempted to shed light on is actually correlated with a longstanding and much known problem in the history of philosophy: the problem of weakness of willpower, or akrasia. I make the case for this interrelatedness by showing that, while they’re not, strictly speaking, the same problem, or mirror problems, weakness of willpower and epistemic inefficacy have a lot in common. In fact, epistemic inefficacy, I submit, is as close as you can get to weakness of willpower in intellectual, or epistemic, contexts, since in those contexts the notion of willpower (ability to control thoughts and actions) is not preponderant. The preponderant notion when it comes to epistemic activity is efficacy (ability to yield the intended results). To accomplish this, I show that there is a good deal of problems with the thing that is normally thought to be, or meant to be, weakness of willpower’s mirror-concept, the so-called “epistemic akrasia”; and I devise a comprehensive presentation of vice epistemology and inquiry epistemology, and of why epistemic inefficacy squares of as an epistemic vice following the tenets of those disciplines